Tinjauan Yuridis Normatif Pasal 1320 Kitab Undang- Undang hukum Perdata Terhadap Modal Ventura Dalam Melakukan Perikatan - jprautor, jprautor (JURNAL PROPERTY RIGHTS, 2015)
Venture Capital Company (Venture Capital Company) is a business entity that conducts of activities in the form of equity financing into a Partnership Company (Investee Company). Venture Capital Company is a company that helps provided capital and technical assistance to customer or it is call the Partnership Company. Venture Capital Company is an alternative non-bank financial institution, in applying for a loan by the entrepreneurs who wants to develop their business. With the process easier to obtain capital from Venture Financing Agency, the debtor who needs capital from Venture Financing Agency is the absence of the element of interest in financing that is given, so that is cool or alternative solutions that do by new businesses with submitted proposal funding to the one of financial institution is Venture Capital Company that be able to help the financing as did for the Bank. Referring to the Minister of Finance Decree No. 1251 of 1988, Venture Capital Company could help capital and technical assistance needed by entrepreneurs and existing businesses to enterprise development in the early stages of their business experiencing financial difficulties. Real forms of participation and support of Venture Capital Company in business development was through equity, convertible bonds, and the pattern of results, where all of the treaties made, had fulfilled the Article 1320 and Article 1338 Civil Law Act.            The approach used is a normative juridical whereas analytical descriptive type of research. Researchers also do a search library and also seek venture Journal in the library. The data obtained and analyzed qualitatively.The results reveal that the agreement is still a lot of venture capital requires an overhaul and dissemination to the wider community that this venture capital company can be known and could be a solution to the problem of venture capital in Indonesia.